Prospectively predicting Pseudomonas aeruginosa infection/s using routine data from the UK cystic fibrosis register. Issue 4 (1st October 2021) - Totton, Nikki; Bradburn, Mike; Hoo, Zhe Hui; Lewis, Jen; Hind, Daniel; Girling, Carla; Shepherd, Elizabeth; Nightingale, Julia; Daniels, Thomas; Dewar, Jane; Dawson, Sophie; Carroll, Mary; et al.
Abstract: Rationale and aims: Lung health of people with cystic fibrosis (PwCF) can be preserved by daily use of inhaled therapy. Adherence to inhaled therapy, therefore, provides an important process measure to understand the success of care and can be used as a quality indicator. Defining adherence is problematic, however, since the number of prescribed treatments varies considerably between PwCF. The problem is less pronounced among those with Pseudomonas aeruginosa (PA), for whom at least three daily doses of nebulized therapy should be prescribed and who thus constitute a more homogeneous group. The UK CF Registry provides routine data on PA status, but data are only available 12 months after collection. In this study, we aim to prospectively identify contemporary PA status from historic registry data. Method: UK CF Registry data from 2011 to 2015 for PwCF aged ≥16 was used to determine a pragmatic prediction rule for identifying contemporary PA status using historic registry data. Accuracy of three different prediction rules was assessed using the positive predictive value (PPV). The number and proportion of adults predicted to have PA infection were determined overall and per center for the selected prediction rule. Known characteristics linked to PA status were explored to ensure the robustness of the prediction rule. Results: Having CF Registry defined chronic PA status in the two previous years is the selected definition to predict a patient will have PA infection within the current year (population‐level PPV = 96%‐97%, centre level PPV = 85%‐100%). This approach provides a subset of data between 1852 and 1872 patients overall and a range of 8 to 279 patients per center. Conclusion: Historic registry data can be used to contemporaneously identify a subgroup of patients with chronic PA. Since this patient group has a narrower treatment schedule, this can facilitate a better benchmarking of adherence across centers.